A Case Report on Bacterial Infections, Newcastle Disease Seroconversion, and Aflatoxin Contamination in a Farm in Southwest Nigeria - Agbajelola, victor; Nwaoha, Precious; Oladeji, Busola (Journal of Poultry Sciences and Avian Diseases, 2025)
This case report details a multifactorial health challenge affecting a 28-week-old flock of 4,524 Arbor Acre broiler breeders on a commercial poultry farm in Southwest Nigeria. The flock presented with respiratory distress, neck twisting, and increased mortality. Postmortem findings included mucoid tracheitis, fibrinous pericarditis, friable livers, and bleached intestines. Diagnostic investigations identified systemic bacterial infection, adequate Newcastle disease vaccine seroconversion (titers ≥1:16), and severe feed contamination with aflatoxin (315 ppb), far exceeding the permissible limit of 20 ppb for poultry feed. Heavy growth of lactose-fermenting bacteria was isolated from tissue samples, prompting antibiotic sensitivity testing, which identified enrofloxacin and ceftriaxone as effective treatments. The elevated aflatoxin levels likely contributed to immunosuppression and impaired flock productivity. Interventions included administering toxin binders, liver tonics, and iodine solutions and replacing contaminated feed. This case underscores the critical importance of integrated diagnostic approaches, targeted antimicrobial therapy, and stringent feed quality control in managing complex poultry health challenges.